PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP HASIL BELAJAR SISWA PADA MATERI BUNYI KELAS VIII MTs NEGERI BATANG ANGKOLA - Lia Purnama Sari (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2024)
This study aims to find out the description of the use of Think Talk Write learning strategy in class VIII MTs NegeriBatangAngkola, to know the students' learning outcomes before and after the sound material using Think Talk Write strategy in class VIII MTs NegeriBatangAngkola, and to know the influence that Significance between Think Talk Write Learning Strategy to physics student learning result of Beep in class VIII MTs NegeriBatangAngkola. The method used in this research is experimental method. The population in this study is all students of class VIII MTs NegeriBatangAngkola consisting of 4 classes, amounting to 118 students. The sampling technique used is random sampling technique. So researchers only take one sample from class VIII-4 that amounted to 30 students. Based on the results of calculations on statistical analysis illustrates that the average value of the use of Think Talk Learning Learning Strategy on Sound Material in Grade VIII MTs NegeriBatangAngkola 3.5 with the category of